Effect of Targeted Educational Program Based on the Transtheoretical Model in Promoting Healthy Nutrition Behaviors in Middle-aged Women in Dehdez, Iran - Kobra Khajehlandi; Akbar Babaei Heydarabadi; Marzieh Araban; Mohammadhosein Haghighizadeh (Hamadan University of Medical Sciences, 2019)
Aims: One of the most important causes of nutritional problems is the discrepancy between the performance of individuals on the basis of knowledge and the lack of proper nutritional knowledge. So, the aim of the current study was to investigate effect of targeted educational program based on the transtheoretical model in promoting healthy nutrition behaviors in middle-aged women in Dehdez, Iran. Materials and Methods: In this semi-experimental study with pre-test post-test design with control group conducted in 2017, 108 middle-aged women referring to Dehdez health center were selected by random sampling and were randomly divided into the experimental (54 subjects) and control (54 subjects) groups. The data were collected, using a nutritional behavior questionnaire in accordance with a transtheoretical model. Educational intervention was performed based on the transtheoretical model within 3 sessions for the experimental group. After 2 months of follow-up, participants completed the research questionnaire again. The data were analyzed by SPSS 22 software, using t-test, Mann-Whitney U test, Chi-square, and Wilcoxon test. Findings: After intervention, the mean scores of benefits and perceived self-efficacy and nutritional behavior in the experimental group was significantly increased compared to the control group (p<0.05). The mean score of the perceived barriers in the experimental group after the intervention was reduced, but this change was not significant in comparison with the control group (p>0.05). Conclusion: Educational program based on the transtheoretical model is effective in promoting healthy nutrition behaviors in the middle-aged women in Dehdez, Iran.